Estudo das condições de secagem por atomização de conídios de Trichoderma harzianum LCB47 - Farias, Virna Luiza de (2009)
In recent years, the world is having a growing concern regarding human activity towards the environment, including the problems related to agriculture. Biological control is, nowadays, a viable and important alternative to chemical defensives. Biological control consists of the used of a living organism (predator, parasite or pathogen) that attacks other unwanted organism without causing damages to the crops. Trichoderma species are known as biological control agents to plant diseases caused by phytopathogenic fungi. T. harzianum is the most applied agent. Conidia are the preferred micropropagules for biological control. For commercialization, biological control products should be stable during storage and should maintain its viability during this period. Drying of the spores allows the preservation of the inoculums for a long period of time maintaining high viability. One of the most used methods for drying spores is spray drying. This work aims to determine the best operating conditions to dry Trichoderma harzianum LCB47 spores, using spray drying, to keep the germinative capacity of the dehydrated product. Experiments were carried out to evaluate the need for encapsulates during drying of the spores. Initially, the inlet and outlet air temperatures in the spray drier were evaluated concerning the survival of the spores and the final dried product moisture content. Several raw materials were tested as encapsulates by means of evaluating their heat capacity (Cp) and by evaluating the level of survival after drying the spores. The inlet and outlet air temperature were evaluated using a factorial design. An evaluation of the viability of the spores during storages was also carried out. The results show the need of the addition of encapsulates for drying spores using spray-drying. The increase between the inlet and outlet air temperatures in the spray-drier resulted in an increase in the final moisture content of the product because of the need to increase the feed flow rate in the spray-drier. Lower outlet air temperatures resulted in higher levels of survival of the spores, and the temperature of 55ºC allowed the best results. Arabic gum was the encapsulate that presented the highest heat capacity and that resulted in the highest protection of the spores during drying. The amount of encapsulate was the most significant factor that influenced in the survival of the spores, while the final moisture content and the water activity were most significantly influenced by the inlet temperature of the air. The spores maintained their viability for a month under refrigeration. The best operating condition to dry spores of T. harzianum LCB47 was obtained applying inlet and outlet air temperatures of respectively 140 and 55ºC, and using maltodextrin as encapsulate. Under this condition, the mean level of survival of the spores was 96%.